2015
DOI: 10.1097/hjh.0000000000000617
|View full text |Cite
|
Sign up to set email alerts
|

Carotid stiffness change over the cardiac cycle by ultrafast ultrasound imaging in healthy volunteers and vascular Ehlers–Danlos syndrome

Abstract: Ultrafast ultrasound imaging can evaluate carotid PWV and its variation over the cardiac cycle. This allowed to demonstrate the age-induced increase of the arterial diastolic-systolic stiffening in healthy people and a lower stiffening in vEDS, both characterized by arterial complications. We believe that this easy-to-use technique could offer the opportunity to go beyond the diastolic PWV to better characterize arterial stiffness change with age or other collagen alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 39 publications
4
62
0
Order By: Relevance
“…Regarding coronary stiffness, if it increases, as it is the case after elongation, PWV will increase. This has been reported for the carotid artery, with significantly lower PWV in early systole compared to end systole (Mirault et al, 2015), and observed herein; there was a trend toward higher CoPWV measured in the elongated artery (decompression: DIC and TM) than when this was measured in a relaxed artery (compression phase: FW). Furthermore, these methods were poorly correlated with the compression FW method.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding coronary stiffness, if it increases, as it is the case after elongation, PWV will increase. This has been reported for the carotid artery, with significantly lower PWV in early systole compared to end systole (Mirault et al, 2015), and observed herein; there was a trend toward higher CoPWV measured in the elongated artery (decompression: DIC and TM) than when this was measured in a relaxed artery (compression phase: FW). Furthermore, these methods were poorly correlated with the compression FW method.…”
Section: Discussionsupporting
confidence: 87%
“…In order to evaluate the accuracy and reliability of the proposed empirical model, reference measurements were obtained by implementing the BH equation given in (4). This approach is recognized as the reference-standard for local PWV measurement [10].…”
Section: Assessment Of Reference Measurementmentioning
confidence: 99%
“…Typically, local PWV from target arterial sites (artery under clinical investigation) is evaluated for a single and the most convenient fiduciary point from each cardiac cycle and averaged over the measurement period. Although such single-value estimates are associated with various pathophysiological conditions [1], instantaneous variation and the degree of change in local PWV within a cardiac cycle have recently been recognized as key measures for advanced cardiovascular screening and diagnosis [3][4][5]. Physiologically, the instantaneous variation in local PWV occurs due to the dependency of vessel elasticity on the arterial transmural pressure (blood pressure (BP)) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, plane wave imaging allows a high-framerate of more than 1 000 images per second (according to depth of interest) against 150 images per second at most for conventional imaging [2]. This increased framerate is useful to image fast phenomena of tissues [3], [4]. Plane wave imaging is used for artery elasticity assessment as well as flow estimation [5], [6].…”
Section: Introductionmentioning
confidence: 99%